Effect of microwave sintering on the properties of copper oxide doped Y-TZP ceramics - Ramesh, Singh; Sara Lee, K.Y.; Tan, Chou Yong; Wong, Yew Hoong; Alengaram, Ubagaram Johnson; Tarlochan, Faris; Ramesh, Subramaniam; Teng, W.D.; Sutharsini, U.; Sarhan, Ahmed Aly Diaa Mohammed (Elsevier, 2018)
The effect of various amounts of copper oxide (CuO) up to 1 wt% on the densification behaviour and mechanical properties of 3 mol% yttria-tetragonal zirconia polycrystal (Y-TZP) were studied by using microwave (MW) sintering method. The MW sintering was performed at temperatures between 1100 °C and 1400 °C, with a heating rate of 30 °C/min. and holding time of 5 min. The beneficial effect of MW in enhancing densification was also compared for the undoped and 0.2 wt% CuO-doped Y-TZP when subjected to conventional sintering (CS) method. The results showed that significant enhancement in the relative density and Vickers hardness were observed for the undoped Y-TZP when MW-sintered between 1100 °C and 1250 °C. It was revealed that the 0.2 wt% CuO-doped Y-TZP and MW sintered at 1250–1300 °C could attain ≥ 99.8% of theoretical density, Vickers hardness of about 14.4 GPa, fracture toughness of 7.8 MPam1/2 and exhibited fine equiaxed tetragonal grain size of below 0.25 µm. In contrast, the addition of 1 wt% CuO was detrimental and the samples exhibited about 50% monoclinic phase upon sintering coupled with poor bulk density and mechanical properties. The study also revealed that the addition of 0.2 wt% CuO and subjected to conventional sintering produced similar densification as that obtained for microwave sintering, thus indicating that the dopant played a more significant role than the sintering method.